Cost-effective concept development using functional modeling guidelines - Cho, Heungjae; Park, Jaeil (Robotics and Computer-Integrated Manufacturing, 2019)
Functional modeling provides a formal approach to early concept development by directly translating customer needs into desired product behavior. By first developing product functionality, the gap between customer needs and product form is lessened. 70–80% of the life-cycle costs of a product are determined by decisions made by designers during the early design stages. Design for assembly (DFA) is a process in which products are designed with ease of assembly in mind. If a product contains fewer parts it will take less time to assemble, thus reducing assembly costs. If functional models can be evaluated based on the three principles of DFA, cost-effective product concepts can be developed earlier in the design stage. Therefore, it is important to estimate the cost-effectiveness of functional models as early as possible. The main goal of this research is to employ the three principles of DFA to evaluate functional models and develop functional modeling guidelines for reducing and integrating functions. We introduce a case study that illustrates how the proposed method works and helps to reduce the number of functions in the assembly process. Conclusions are then discussed and future research is described.
Keywords: Assembly process; Concept development; Design for assembly; Developing product; Early design stages; Ease of assemblies; Functional model; Product concepts; Concept development; Cost-effectiveness; Design for assembly; Functional modeling; Functional modeling guidelines